(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Heteroptera in two different plant mixtures are considered. The first plot is a mixture of species with different flowering periods, the second one presents mainly Gramineae. As foreseen, the first plot presents a higher number of species of Heteroptera and in the second. one the species are mainly phytophagous rather than predaceous.